Bioinformatics and the Metaverse: Are We Ready? - Taylor, Stephen; Soneji, Shamit (Frontiers in Bioinformatics, 2022)
Immersive technologies after a number of false starts throughout the years appear to be gaining traction, and COVID-19 has forced humanity to think about new ways of working globally without physically being present with other people. Immersive or eXtended Reality (XR) systems are defined as Virtual Reality (VR) , Augmented Reality(AR) and Mixed Reality(MR). Previously seen as mainly for gaming, commercial and research institutions are investigating XR solutions to solve real world problems from training, simulation, mental health, and studying disease progression (Sea Hero Quest). More recently large corporations such as Microsoft and Meta have announced they are developing the metaverse as a new paradigm to interact with the digital world. This article will look at how immersive technologies are being used in visualization in research, the pros and cons of this technology, and what the future may hold.